2011
DOI: 10.1007/s12311-011-0319-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thimerosal Exposure Results in Aberrant Cerebellar Oxidative Stress, Thyroid Hormone Metabolism, and Motor Behavior in Rat Pups; Sex- and Strain-Dependent Effects

Abstract: Methylmercury (Met-Hg) and ethylmercury (Et-Hg) are powerful toxicants with a range of harmful neurological effects in humans and animals. While Met-Hg is a recognized trigger of oxidative stress and an endocrine disruptor impacting neurodevelopment, the developmental neurotoxicity of Et-Hg, a metabolite of thimerosal (TM), has not been explored. We hypothesized that TM exposure during the perinatal period impairs central nervous system development, and specifically the cerebellum, by the mechanism involving o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…Those studies have yielded significant pathology or clinical symptoms in mice,[36] rats,[373839] hamsters,[40] and monkeys[41] that are consistent with those observed in specific delays in development following exposure to Thimerosal-containing vaccines mimicking the US routine childhood vaccination schedule of the 1990s.…”
Section: Discussionmentioning
confidence: 57%
“…Those studies have yielded significant pathology or clinical symptoms in mice,[36] rats,[373839] hamsters,[40] and monkeys[41] that are consistent with those observed in specific delays in development following exposure to Thimerosal-containing vaccines mimicking the US routine childhood vaccination schedule of the 1990s.…”
Section: Discussionmentioning
confidence: 57%
“…In that study, Sulkowski et al (2012) found a greater disruption of hormones in the brain of male rats exposed to Thimerosal, where local intra-brain conversion of thyroxine to the active hormone, 3',3,5-triiodothyronine (T3), was significantly decreased (60.9%) in Thimerosal-exposed SHR male rat pups. However, cognitive deficits from Thimerosal exposure were found in both male and female rats.…”
Section: Ethylmercury or Thimerosalmentioning
confidence: 88%
“…It is widely recognized that younger, more rapidly developing brains are more vulnerable to toxic exposures, particularly to mercury exposure (Hewitson et al, 2010;Ida-Eto et al, 2011;Olczak et al, 2011;Sulkowski et al, 2012;Blanusa et al, 2012;Ida-Eto et al, 2013). In a 1997 publication, Grandjean et al note that prenatal exposure to methylmercury is associated with significant detectable neurologic performance deficits at age 7, as measured via neuropsychological evaluation.…”
Section: Introductionmentioning
confidence: 99%